Role of Planning in Industrial Development - Planning Commission (Planning Commission, 1969)
Looking al the galaxy of eminent scholars who have preceded me, I deem it a great honour to have the privilege to deliver the Sastri Memorial lectures. Shri V. S. Srinivasa Sastri was one of the most brilliant intellectuals of this century who dedicated his life to public service. He was a great social reformer and was the moving spirit of the Servants of India Society. In politics he stood for liberalism and constitutionalism and made valuable contribution to the evolution of the political reforms in the earlier period. His mastery over the English language and his power of eloquence invited the highest appreciation. Above all, he was a courageous statesman, who, sustained by the strength of his convictions, battled throughout his life for the political and social advancement of his country. Il is only appropriate that we remember and pay homage to this great Indian.
Role of Planning in Industrial Development
Planning Commission